Contribution of Regulatory T Cell Methylation Modifications to the Pathogenesis of Allergic Airway Diseases - Jiani Li; Jichao Sha; Liwei Sun; Dongdong Zhu; Cuida Meng (Journal of Immunology Research)
Regulatory T (Treg) cells are a subtype of CD4+ T cells that play a significant role in the protection from autoimmunity and the maintenance of immune tolerance via immune regulation. Epigenetic modifications of Treg cells (i.e., cytosine methylation at the promoter region of the transcription factor, Forkhead Box P3) have been found to be closely associated with allergic diseases, including allergic rhinitis, asthma, and food allergies. In this study, we highlighted the recent evidence on the contribution of epigenetic modifications in Treg cells to the pathogenesis of allergic diseases. Moreover, we also discussed directions for future clinical treatment approaches, with a particular emphasis on Treg cell-targeted therapies for allergic disorders.